Genomic Sequencing of Phyllosticta citriasiana Provides Insight Into Its Conservation and Diversification With Two Closely Related Phyllosticta Species Associated With Citrus - Wang, Mingshuang; Liu, Bei; Ruan, Ruoxin; Zeng, Yibing; Luo, Jinshui; Li, Hongye (Frontiers in Microbiology, 2020)
Phyllosticta capitalensis, Phyllosticta citricarpa, and Phyllosticta citriasiana are three very important Phyllosticta species associated with citrus. P. capitalensis is an endophyte fungus of citrus while P. citricarpa can cause black spot of citrus (e.g. oranges and mandarins). P. citriasiana was identified recently which is the causal agent of the pomelo tan spot. Here, we present the ~34Mb genome of P. citriasiana. The genome is organized in 92 contigs, encompassing 9202 predicted genes. Comparative genomic analyses with two other Phyllosticta species (P. citricarpa and P. capitalensis) associated with citrus was conducted to understand their evolutionary conservation and diversification. Pair-wise genome alignments revealed that these species are highly syntenic. All species encode similar numbers of CAZymes and secreted proteins. However, the molecular functions of the secretome showed that each species contains some enzymes with distinct activities. The three Phyllosticta species investigated shared a core set of 7261 protein families. P. capitalensis had the largest set of orphan genes (1991), in complete contrast to that of P. citriasiana (364) and P. citricarpa (262). Most of the orphan genes are functionally unknown, but they contain a certain number of species-specific secreted proteins. A total of 23 secondary metabolites biosynthesis clusters were identified in the three Phyllosticta species, 21 of them being highly conserved among these species while the remaining 2 showed whole cluster gain and loss polymorphisms or gene content polymorphisms. Taken together, our study reveals insights into the genetic mechanisms of host adaptation of 3 species of Phyllosticta associated with citrus and paves the way to identify effectors that function in infection of citrus plants.